German FDI in the Czech Republic: employment effects in the home country - Schäffler, Johannes; Moritz, Michael (Nürnberg, 2018)
"Do investments in the Czech Republic lead to employment growth or employment losses in the German firms involved? To address this question, a unique database about German firms with foreign direct investment (FDI) in the Czech Republic and firms without FDI in any country has been established within the IAB-ReLOC project. By developing a new method for linking firm-level data with establishment-level data of the Institute for Employment Research (IAB), this database is now linked with the IAB employment data. As the exact dates of the investments in the Czech Republic are known, the employment development of firms with Czech affiliates and firms without FDI is compared for the same time periods. The analysis shows that the two observation groups actually develop differently. In the years after the investment, the employment of multinational enterprises (MNEs) in the home country shrinks relative to the employment of the reference group (non-MNEs). The negative trend continues for up to five years. However, not all types of jobs are affected adversely. The downward trend refers to medium- and low-skilled workers only, whereby the demand for high-skilled workers even increases after the investment."